DETERMINATION OF ANTHOCYANINS IN SOME VEGETABLES AND FRUITS BY DERIVATIVE SPECTROPHOTOMETRIC METHOD - Sakar, Dolunay; Karaoglan, Guelnur Keser; Gumrukcu, Gulsah; Ozgur, Mahmure Ustun (WALTER DE GRUYTER GMBH, 2008)
Anthocyanins (E 163) have been determined in red cabbage, blackberry, morello cherry, grape and sumac fruit by first order derivative spectrophotometry without using any separation or background correction techniques and reagents. The method is based on the measurement of the distances between two extremum values (peak-to-peak amplitudes) in the first order derivative spectra of the extracts. In the developed method, perchloric acid (5% v/v) was found to be the most suitable extraction solution. The extraction time was determined as 10 minutes in fresh fruits and vegetables and in dried ones 20 minutes. In the first order derivative spectrum, the maximum at 490.5 nm and the minimum at 550.2 nm were used for the quantitative determination of anthocyanins in red cabbage, sumac fruit, blackberry, morello and grape. A calibration curve was constructed for the 100-500 mu g mL(-1) concentration range. The calibration equation and regression coefficient obtained from the first derivative spectra is D-1(490.5-550.2)= 0.0543C + 0.926, r=0.9999.
Keywords: Anthocyanins determination; derivative spectrophotometry; fruits; vegetables; ASCORBIC-ACID; RED WINES; LIQUID-CHROMATOGRAPHY; BACKGROUND CORRECTION; SOFT DRINKS; JUICES; CLASSIFICATION; PIGMENTS; Chemistry